(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
This article deals with the structural and semantic analyses of Lutsk’s ergonims (for example, names of dining-rooms). Have considered the views of linguists at understanding of the term ergonim. Analyzed 275 names of restaurants, cafes, bars, pizzerias and found that these structural ergonims are divided into one-, two-, three-and multicomponent.